Cyclodextrin-based Schiff base pro-fragrances: Synthesis and release studies - Palágyi, Attila; Jindřich, Jindřich; Dian, Juraj; Fourmentin, Sophie (Beilstein Journal of Organic Chemistry, 2022)
A simple method for the preparation of β-cyclodextrin derivatives containing covalently bonded aldehydes via an imine bond was developed and used to prepare a series of derivatives from 6I-amino-6I-deoxy-β-cyclodextrin and the following volatile aldehydes – cinnamaldehyde, cyclamen aldehyde, lilial, benzaldehyde, anisaldehyde, vanillin, hexanal, heptanal, citral, and 5-methylfurfural. Subsequently, the rate of release of the volatile compound from selected pro-fragrances, as a function of the environment (solvent, pH), was studied by 1H NMR spectroscopy (for benzaldehyde) and static headspace-gas chromatography (for benzaldehyde, heptanal, and 5-methylfurfural). The aldehyde release rate from the imine was shown to depend substantially on the pH from the solution and the air humidity from the solid state.
Keywords: aldehyde; controlled release; cyclodextrin; imine; kinetics; pro-fragrance; Schiff base